Application of computers in artificial intelligence in the context of big data - Sun, Manman; Cui, Suli; Qiu, Bin (Applied mathematics and nonlinear sciences, 2024)
To make the computer useful in the field of artificial intelligence in the context of big data. In this paper, based on the analysis and comparison of the big data algorithm model and artificial intelligence algorithm in computers, we propose an algorithm based on a decision tree and logistic regression model in big data to query literature papers in the field of artificial intelligence as an example and compare and analyze the accuracy, accuracy, completeness, and F1 value of the obtained data through two categories of experiments. The experimental results show that the decision tree and logistic regression algorithm model based on big data can make the data finding accuracy of 89%, accuracy of 92%, and completeness of 87%, and optimize the speed and quality of the computer algorithm in the process of processing big data. This shows that the computer in the context of big data can provide access to data through algorithmic models in the field of artificial intelligence, which can improve the accuracy and authenticity of data sources and provide data support for in-depth research in the field of artificial intelligence.